The market for animal-source foods in Uganda: Looking beyond quantity: Rapid appraisal of consumer preferences for retail outlets, retail forms and safety and quality attributes - Baker, Derek; Mtimet, Nadhem; Pica-Ciamarra, U.; Jagwe, J. (2013)
This paper presents the results of a rapid consumer survey undertaken in Uganda. The survey aimed at identifying preferred quality and safety attributes, retail forms and retail outlets for major livestock products and by type of consumers. Results of the survey, combined with nationally representative household datasets, allows description of both the quantitative and qualitative dimensions of the developing market for animal-source foods, which is anticipated to provide major business opportunities for small-scale livestock producers in the short and medium terms.